TPU black non-heat-absorption composite material applied to automobile top interior trim parts and preparation method of TPU black non-heat-absorption composite material

By mixing with polyacrylin resin through thermoplastic polyurethane resin, and added components such as dioxide-Elot Stone dual-network gas gel, it solves the problem of insufficient thermal absorption of the interior of the car, and realizes the height of composite materials. The performance of heat resistance, thermal insulation and flame retardant is suitable for the interior of the car.

CN119350838APending Publication Date: 2025-01-24GUANGDONG GERUI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411705662.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art involves less research on the non-absorbing properties of automobile roof interior parts, especially the insufficient thermal insulation properties of thermoplastic polyurethane composite materials.

Method used

Use thermoplastic polyurethane resin (TPU) to mix with polypropylene resin (PP), and add components such as dioxide-Elot Stone dual-network gas gel, phosphate, etc. Burning performance.

Benefits of technology

The prepared composite materials have excellent heat resistance and thermal insulation performance. The flame retardant performance reaches V-0 level. It is suitable for the interior parts of the car of the car, which effectively avoids the temperature in the car and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure AK1QWHZOT3ODDVXFJ5H0TRMNRAF3H5PPNVFM1BAF
    Figure AK1QWHZOT3ODDVXFJ5H0TRMNRAF3H5PPNVFM1BAF
Patent Text Reader

Abstract

The invention discloses a TPU black non-heat-absorption composite material applied to automobile top interior trim parts. Comprising the following components in parts by weight: 100 to 120 parts of thermoplastic polyurethane resin, 20 to 30 parts of polypropylene resin, 10 to 15 parts of glycidyl methacrylate grafted polyolefin elastomer, 8 to 12 parts of zirconium dioxide-halloysite dual-network aerogel, 3 to 6 parts of black master batch, 2 to 5 parts of triphenyl phosphate, 0.5 to 1 part of antioxidant and 0.3 to 0.7 part of lubricant, the prepared composite material has good mechanical properties and excellent heat resistance and heat insulation performance, and the flame retardant property also reaches the V-0 level. The zirconium dioxide-halloysite double-network aerogel is used as an additive and can play a synergistic effect with the flame retardant to improve the flame retardance of the composite material, and the safety can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer composite materials, and in particular to a TPU black non-absorbent composite material used for automobile top interior decoration parts and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane (TPU) is a material between rubber and plastic, with excellent wear resistance, tear resistance, chemical resistance and softness. It also has good mechanical strength, oil resistance, chemical resistance, and thermal oxidation stability; it has a wide range of applications in industry. TPU has been widely used in automotive top interior parts due to its excellent comprehensive performance, environmentally friendly recyclability, and lightweight characteristics, and with the development of technology and the improvement of consumers' requirements for automotive interior performance.

[0003] Patent CN 110982239 A discloses a high-blackness PC / ABS alloy material for automotive interior parts and a preparation method thereof, wherein the high-blackness PC / ABS alloy material for automotive interior parts is prepared by distributing and melting polycarbonate, ultra-high flow polycarbonate, acrylonitrile-styrene copolymer, pH value regulator, surface treatment agent, carbon black, high rubber powder and MBS resin. This patent solves the technical problem of insufficient blackness caused by surface fogging due to the precipitation of scratch-resistant agent; however, it does not involve improvements in non-absorption-related aspects.

[0004] Patent CN 102617930 B discloses a decorative material for automobiles and a manufacturing method thereof. The raw materials of the decorative material are formulated by weight as follows: 65-75 parts of polypropylene resin, 5-25 parts of thermoplastic polyurethane resin, 5-15 parts of saturated ethylene-octene copolymer, 3-6 parts of nano titanium dioxide, 10-15 parts of toughening agent, 5-10 parts of nucleating agent, 5-10 parts of grafting compatibilizer, 0.4-0.6 parts of compound stabilizer, and 0.3-0.7 parts of coupling agent. The formula design involves scratch resistance, wear resistance, dirt resistance, no odor, aging resistance and molding processability, meeting people's high requirements for automobile interior decoration and the purpose of low price.

[0005] There are many studies on automotive interior parts in the existing technology. With the development of new energy electric vehicles in my country, the demand for materials is increasing. There are few studies on automotive top interior parts, especially thermoplastic polyurethane composite materials, and even fewer studies on non-absorption properties. Summary of the invention

[0006] In view of the needs and deficiencies of the prior art, the present invention discloses a TPU black non-absorptive composite material for automobile top interior decoration parts and a preparation method thereof. The prepared composite material has good mechanical properties, excellent heat resistance and heat insulation properties, and the flame retardant property also reaches V-0 level.

[0007] In order to solve the technical problem of this application and achieve the above-mentioned purpose, the technical solution provided by the present invention is as follows: A TPU black non-absorbent composite material used for automobile top interior decoration parts, comprising the following components in parts by weight: 100-120 parts of thermoplastic polyurethane resin, 20-30 parts of polypropylene resin, 10-15 parts of glycidyl methacrylate grafted polyolefin elastomer, 8-12 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 3-6 parts, 2-5 parts of triphenyl phosphate, 0.5-1 part antioxidant Lubricant 0.3-0.7 parts.

[0008] Furthermore, the composite material is composed of the following components in parts by weight: 100-120 parts of thermoplastic polyurethane resin, 20-30 parts of polypropylene resin, 10-15 parts of glycidyl methacrylate grafted polyolefin elastomer, 8-12 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 3-6 parts, 2-5 parts of triphenyl phosphate, 0.5-1 part antioxidant Lubricant 0.3-0.7 parts.

[0009] Furthermore, the composite material is composed of the following components in parts by weight: 105-115 parts of thermoplastic polyurethane resin, 23-27 parts of polypropylene resin, Glycidyl methacrylate grafted polyolefin elastomer 12-13 parts, 9-10 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 4-5 parts, 3-4 parts of triphenyl phosphate, 0.7-0.8 parts of antioxidant, Lubricant 0.4-0.6 parts.

[0010] Furthermore, the antioxidant is selected from antioxidant 1076 and antioxidant 168.

[0011] Furthermore, the lubricant is selected from methylene bisstearic acid amide and N,N-ethylene bisstearic acid amide.

[0012] Furthermore, the preparation steps of the zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolving 5 parts of polyethylene glycol in 100 parts of water at 80°C and stirring vigorously for 2 hours; dispersing 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stirring for 10 minutes to obtain a uniform suspension. The polyethylene glycol solution and the halloysite nanotube suspension are mixed, then poured into a container and subjected to ultrasonic dispersion treatment for 20 minutes. Then, 0.5 parts of saturated borax solution are added dropwise to the mixture, and the mixture is stirred continuously until it becomes viscous, and then poured into a mold. The mold is placed in a freezer at -20°C for 24 hours and dried in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) 10 parts of tetra-tert-butoxy zirconium, 20 parts of anhydrous ethanol and 15 parts of water are added to a reaction container, stirred at 40°C for 15 minutes, and then slowly added with a concentration of 0.05 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 minutes to obtain ZrO2 sol. Place ZrO2 sol and halloysite-polyethylene glycol first network aerogel in a container in a vacuum environment, immerse the halloysite-polyethylene glycol first network aerogel in ZrO2 sol, and after completely removing air bubbles, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly for 30 minutes. The sol becomes a wet gel, and then it is immersed in ethanol at room temperature for aging for 24 hours. The aged CO2 supercritical drying tank is supercritically dried to finally obtain zirconium dioxide-halloysite double network aerogel.

[0013] The technical idea of ​​this application is to select aerogel to improve the non-absorptive performance of the composite material. The aerogel is composed of nanometer and / or micrometer-scale particles, and there are a large number of gaps between the particles. The air or other gases in the gaps usually have very low thermal conductivity, which gives the aerogel extremely low thermal conductivity; in addition, the network structure in the aerogel provides a complex path and increases the path length of heat transfer, which increases the difficulty of heat transfer, thereby improving the thermal insulation effect. This application is specifically based on halloysite aerogel, and further utilizes the excellent physical properties and thermal insulation properties of zirconium dioxide. The advantages of the two are combined in the form of aerogel to form a double-network aerogel, which better improves the heat resistance and thermal insulation properties of the composite material, so that it has good non-absorptive performance.

[0014] In the present application, triphenyl phosphate is used as a flame retardant, which can effectively improve the flame retardant properties of the composite material; at the same time, the zirconium dioxide-halloysite double network aerogel can also play a good flame retardant role, and the two synergistically improve the overall flame retardant properties of the composite material.

[0015] The present invention forms a polymer composite material by blending thermoplastic polyurethane resin (TPU) and polypropylene resin (PP), which effectively brings into play the advantages of both and can make up for their respective shortcomings.

[0016] The present invention adopts glycidyl methacrylate grafted polyolefin elastomer (GMA-g-POE) as a toughening and compatibilizing agent, which can effectively improve the compatibility of TPU and PP, thereby improving the morphology and mechanical properties of the blend; and provides a basic guarantee for the application of composite materials.

[0017] A method for preparing a TPU black non-absorbent composite material used for automobile top interior trims, comprising the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) pouring thermoplastic polyurethane resin and zirconium dioxide-halloysite double network aerogel into a stirring device and stirring them evenly to form material group A; (3) Pour polypropylene resin, glycidyl methacrylate grafted polyolefin elastomer, black masterbatch, triphenyl phosphate, antioxidant, and lubricant into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0018] Furthermore, the set temperature of the twin-screw extruder is: section one: 170-180°C, section two: 170-180°C, section three: 175-185°C, section four: 180-190°C, section five: 180-190°C, section six: 165-175°C, section seven: 165-175°C, section eight: 165-175°C, section nine: 170-180°C, and die head: 175-185°C.

[0019] Furthermore, the rotation speed of the twin-screw extruder is 350-450 rpm.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) With respect to automobile top interior parts, the present invention provides a polymer composite material formed by blending thermoplastic polyurethane resin and polypropylene resin. The composite material has good mechanical properties, high blackness, and excellent non-absorption of heat. As automobile top interior parts, its excellent heat resistance and heat insulation effectively prevent the temperature inside the car from rising.

[0021] (2) The creative use of zirconium dioxide-halloysite double network aerogel as an additive can work synergistically with flame retardants to improve the flame retardancy of composite materials, which can effectively improve safety.

[0022] (3) Composite materials with high blackness have a good appearance and can enhance the overall visual effect of the interior of the car. The black color also gives the interior parts good dirt resistance. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] Main ingredients: Thermoplastic polyurethane resin is Covestro Bayer TPU359X from Germany. The polypropylene resin is Total (USA) PP3378, Halloysite nanotubes are products of Zhengzhou Golden Sunshine Ceramics Co., Ltd. The glycidyl methacrylate grafted polyolefin elastomer is SH-915 from Foshan Ruisheng Plastic Co., Ltd. The black masterbatch is the high-concentration and high-brightness black masterbatch F-26 purchased from Hangzhou Caibiao Masterbatch Co., Ltd.

[0025] Preparation of Zirconium Dioxide-Halloysite Double Network Aerogel: The preparation steps of zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolve 5 parts of polyethylene glycol in 100 parts of water at 80°C and stir vigorously for 2 hours; disperse 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stir for 10 minutes to obtain a uniform suspension. Mix the polyethylene glycol solution and the halloysite nanotube suspension, pour them into a container, and disperse them in ultrasound for 20 minutes. Then add 0.5 parts of saturated borax solution to the mixture, stir continuously until it becomes sticky, and then pour it into a mold. Place the mold in a freezer at -20°C for 24 hours and dry it in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) add 10 parts of tetra-tert-butoxyzirconium, 20 parts of anhydrous ethanol and 15 parts of water to the reaction container, stir at 40°C for 15 minutes, and then slowly add a concentration of 0.01 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 minutes to obtain ZrO2 sol. Place ZrO2 sol and halloysite-polyethylene glycol first network aerogel in a container in a vacuum environment, immerse the halloysite-polyethylene glycol first network aerogel in ZrO2 sol, and after completely removing air bubbles, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly for 30 minutes. The sol becomes a wet gel, and then it is immersed in ethanol at room temperature for aging for 24 hours. The aged CO2 supercritical drying tank is supercritically dried to finally obtain zirconium dioxide-halloysite double network aerogel.

[0026] Unless otherwise specified, the aerogels used in the following examples and comparative examples are prepared as described above.

[0027] A TPU black non-absorbent composite material used for automobile top interior decoration parts, composed of the following components in parts by weight: 100 parts of thermoplastic polyurethane resin, 20 parts of polypropylene resin, Glycidyl methacrylate grafted polyolefin elastomer 10 parts, 8 parts of zirconium dioxide-halloysite double network aerogel, 3 parts of black masterbatch, 2 parts of triphenyl phosphate, 0.5 parts of antioxidant, 0.3 parts of lubricant.

[0028] Wherein, the antioxidant is selected from antioxidant 1076; the lubricant is selected from methylene bisstearamide.

[0029] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) pouring thermoplastic polyurethane resin and zirconium dioxide-halloysite double network aerogel into a stirring device and stirring them evenly to form material group A; (3) Pour polypropylene resin, glycidyl methacrylate grafted polyolefin elastomer, black masterbatch, triphenyl phosphate, antioxidant, and lubricant into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0030] Among them, the set temperatures of the twin-screw extruder are: section one: 170°C, section two: 170°C, section three: 175°C, section four: 180°C, section five: 180°C, section six: 165°C, section seven: 165°C, section eight: 165°C, section nine: 170°C, and die head: 175°C.

[0031] Wherein, the rotation speed of the twin-screw extruder is 350 rpm.

[0032] A TPU black non-absorbent composite material used for automobile top interior decoration parts, composed of the following components in parts by weight: 120 parts of thermoplastic polyurethane resin, 30 parts of polypropylene resin, Glycidyl methacrylate grafted polyolefin elastomer 15 parts, Zirconium dioxide-halloysite double network aerogel 12 parts, Black masterbatch 6 parts, 5 parts of triphenyl phosphate, 1 part antioxidant, 0.7 parts of lubricant.

[0033] Wherein, the antioxidant is selected from antioxidant 168; and the lubricant is selected from N,N-ethylene bisstearamide.

[0034] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) pouring thermoplastic polyurethane resin and zirconium dioxide-halloysite double network aerogel into a stirring device and stirring them evenly to form material group A; (3) Pour polypropylene resin, glycidyl methacrylate grafted polyolefin elastomer, black masterbatch, triphenyl phosphate, antioxidant, and lubricant into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0035] Among them, the set temperatures of the twin-screw extruder are: section one: 180°C, section two: 180°C, section three: 185°C, section four: 190°C, section five: 190°C, section six: 175°C, section seven: 175°C, section eight: 175°C, section nine: 180°C, and die head: 185°C.

[0036] Wherein, the rotation speed of the twin-screw extruder is 450 rpm.

[0037] A TPU black non-absorbent composite material used for automobile top interior decoration parts, composed of the following components in parts by weight: 110 parts of thermoplastic polyurethane resin, 25 parts of polypropylene resin, Glycidyl methacrylate grafted polyolefin elastomer 12 parts, Zirconium dioxide-halloysite double network aerogel 10 parts, Black masterbatch 4.5 parts, 3.5 parts of triphenyl phosphate, 0.7 parts of antioxidant, 0.5 parts of lubricant.

[0038] Wherein, the antioxidant is selected from antioxidant 1076; and the lubricant is selected from N,N-ethylene bisstearamide.

[0039] The method for preparing the composite material comprises the following steps: (1) Weigh the components in the appropriate proportions and set aside; (2) pouring thermoplastic polyurethane resin and zirconium dioxide-halloysite double network aerogel into a stirring device and stirring them evenly to form material group A; (3) Pour polypropylene resin, glycidyl methacrylate grafted polyolefin elastomer, black masterbatch, triphenyl phosphate, antioxidant, and lubricant into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

[0040] Furthermore, the set temperatures of the twin-screw extruder are: section one: 175°C, section two: 175°C, section three: 180°C, section four: 185°C, section five: 185°C, section six: 170°C, section seven: 170°C, section eight: 170°C, section nine: 175°C, and die head: 180°C.

[0041] Furthermore, the rotation speed of the twin-screw extruder is 400 rpm.

[0042] Comparative Example 1 Comparative Example 1 is consistent with Example 3, except that no zirconium dioxide-halloysite double network aerogel is added in Comparative Example 1.

[0043] Comparative Example 2 Comparative Example 2 is consistent with Example 3, except that no triphenyl phosphate is added in Comparative Example 2.

[0044] The composite material prepared above was tested for performance. The composite material was first made into standard test specimens according to the test standards of various countries. The thermal insulation was characterized by measuring its thermal conductivity with a thermal conductivity meter. The temperature rise value (△T) was measured after the standard test specimen was irradiated with a UV lamp (40W) for 3h (irradiation distance 50mm). The L value was measured according to GB / T7921-2008 to characterize the blackness. The specific test results are recorded in Table 1.

[0045] Table 1 It can be seen from the above test data that the composite material prepared by the present invention has good mechanical properties, and its tensile strength can reach 50MPa and its Shore A hardness can reach 80, which can meet the basic application requirements of automobile top interior parts; Comparative Example 1 does not contain zirconium dioxide-halloysite double network aerogel, and the composite material is lower than that of Example 3, indicating that zirconium dioxide-halloysite double network aerogel can also improve its mechanical properties to a certain extent.

[0046] The flame retardant grades of comparative examples 1-2 are only V-2 and V-1, which are significantly lower than V-0 of example 3, indicating that zirconium dioxide-halloysite double network aerogel and triphenyl phosphate can play the role of flame retardants in the composite material, and in the present invention, the effect of zirconium dioxide-halloysite double network aerogel on flame retardancy is higher than that of triphenyl phosphate; in addition, the joint use of zirconium dioxide-halloysite double network aerogel and triphenyl phosphate can effectively play a synergistic role to improve the flame retardant properties of the composite material.

[0047] From the test results of thermal conductivity and temperature rise value, it can be seen that the composite material prepared by the present invention has a lower thermal conductivity, indicating that the composite material has excellent thermal insulation performance; at the same time, the temperature rise value data can also support this view. The thermal conductivity of comparative example 1 is much lower than that of example 3, which shows that the zirconium dioxide-halloysite double network aerogel plays a decisive role in the thermal insulation performance in this application.

[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A TPU black non-absorbent composite material used for automobile top interior trim, characterized in that: According to parts by weight, it includes the following components: 100-120 parts of thermoplastic polyurethane resin, 20-30 parts of polypropylene resin, 10-15 parts of glycidyl methacrylate grafted polyolefin elastomer, 8-12 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 3-6 parts, 2-5 parts of triphenyl phosphate, 0.5-1 part antioxidant Lubricant 0.3-0.7 parts.

2. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: 100-120 parts of thermoplastic polyurethane resin, 20-30 parts of polypropylene resin, 10-15 parts of glycidyl methacrylate grafted polyolefin elastomer, 8-12 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 3-6 parts, 2-5 parts of triphenyl phosphate, 0.5-1 part antioxidant Lubricant 0.3-0.7 parts.

3. The composite material according to claim 1, characterized in that According to parts by weight, it is composed of the following components: 105-115 parts of thermoplastic polyurethane resin, 23-27 parts of polypropylene resin, Glycidyl methacrylate grafted polyolefin elastomer 12-13 parts, 9-10 parts of zirconium dioxide-halloysite double network aerogel, Black masterbatch 4-5 parts, 3-4 parts of triphenyl phosphate, 0.7-0.8 parts of antioxidant, Lubricant 0.4-0.6 parts.

4. The composite material according to any one of claims 1 to 3, characterized in that: The antioxidant is selected from antioxidant 1076 and antioxidant 168.

5. The composite material according to any one of claims 1 to 3, characterized in that: The lubricant is selected from methylene bisstearic acid amide and N,N-ethylene bisstearic acid amide.

6. The composite material according to any one of claims 1 to 3, characterized in that: The preparation steps of the zirconium dioxide-halloysite double network aerogel are as follows: (1) dissolving 5 parts of polyethylene glycol in 100 parts of water at 80°C and stirring vigorously for 2 hours; dispersing 10 grams of halloysite nanotubes in 100 parts of water at 40°C and stirring for 10 minutes to obtain a uniform suspension. The polyethylene glycol solution and the halloysite nanotube suspension are mixed, then poured into a container and subjected to ultrasonic dispersion treatment for 20 minutes. Then, 0.5 parts of saturated borax solution are added dropwise to the mixture, and the mixture is stirred continuously until it becomes viscous, and then poured into a mold. The mold is placed in a freezer at -20°C for 24 hours and dried in a vacuum freeze dryer for 8 hours to obtain the first halloysite-polyethylene glycol network aerogel; (2) 10 parts of tetra-tert-butoxy zirconium, 20 parts of anhydrous ethanol and 15 parts of water are added to a reaction container, stirred at 40°C for 15 minutes, and then a concentration of 0.05 mol·L -1 / hydrochloric acid solution, adjust the pH to 2.6, and continue stirring for 20 minutes to obtain ZrO2 sol. Place ZrO2 sol and halloysite-polyethylene glycol first network aerogel in a container in a vacuum environment, immerse the halloysite-polyethylene glycol first network aerogel in ZrO2 sol, and after completely removing air bubbles, add ammonia solution to the sol until the pH is 7.2, and stir the solution evenly for 30 minutes. The sol becomes a wet gel, and then it is immersed in ethanol at room temperature for aging for 24 hours. The aged CO2 supercritical drying tank is supercritically dried to finally obtain zirconium dioxide-halloysite double network aerogel.

7. A method for preparing a TPU black non-absorbent composite material used for automobile top interior trim, characterized in that: The following steps are involved: (1) Weigh the components in the appropriate proportions and set aside; (2) pouring thermoplastic polyurethane resin and zirconium dioxide-halloysite double network aerogel into a stirring device and stirring them evenly to form material group A; (3) Pour polypropylene resin, glycidyl methacrylate grafted polyolefin elastomer, black masterbatch, triphenyl phosphate, antioxidant, and lubricant into a stirring device and stir evenly to form material group B; (4) Material group A is fed from the main feed of a twin-screw extruder, and material group B is fed from the side feed of the twin-screw extruder, and the materials are melted, mixed, and extruded through the twin-screw extruder to obtain a composite material.

8. The method for preparing a composite material according to claim 7, characterized in that: The set temperatures of the twin-screw extruder are: section one: 170-180°C, section two: 170-180°C, section three: 175-185°C, section four: 180-190°C, section five: 180-190°C, section six: 165-175°C, section seven: 165-175°C, section eight: 165-175°C, section nine: 170-180°C, and die head: 175-185°C.

9. The method for preparing a composite material according to claim 7, characterized in that: The rotation speed of the twin-screw extruder is 350-450 rpm.

Citation Information

Patent Citations

  • A decorative material for automobiles and its manufacturing method

    CN102617930B

  • High-blackness PC / ABS alloy material for automotive upholstery and preparation method thereof

    CN110982239A